Computational Insights on Periodicity in Bonding and Lewis Acidity and Basicity of the p‐Block Trispyrazolylborate Complexes. Issue 2 (7th November 2022) - Prakash, Rini; Mohamed, Amina; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract: Hydrotris(pyrazolyl)borate ligands are a popular class of ligands to stabilize both Lewis acidic and Lewis basic main group compounds. In this work we analyze the low‐valent group 13–15 compounds of hydrotris(3, 5‐dimethyl‐pyrazolyl)borate ligand, [Tp*E] x, 1–15 (E=group 13 element, x=0; E=group 14 element, x=1+ ; E=group 15 element, x=2+) based on density functional theory. A periodic increment in intrinsic Lewis acidity is observed down the group due to increased E−N bond polarization towards nitrogen, resulting in lower energy secondary binding sites. However, global Lewis acidity measures in terms of FIA and IIA indicate the dependency on the choice of the nucleophile. In general, this study underscores the potential of the Tp* ligand in stabilizing the reactive low‐valent p‐block elements. Abstract : A detailed computational analysis of low‐valent p‐block compounds of hydrotris(3, 5‐dimethyl‐pyrazolyl)borate ligand, [Tp*E] x, (E=group 13 element, x=0; E=group 14 element, x=1+ ; E=group 15 element, x=2+) shows increasing intrinsic Lewis acidity down the group as E−N bond polarizes.